Molecular targets for cancer therapy in the PI3K/AKT/mTOR pathway - Polivka, Jiri; Janku, Filip (Pharmacology & therapeutics, 2014)
Aberrations in various cellular signaling pathways are instrumental in regulating cellular metabolism, tumor development, growth, proliferation, metastasis and cytoskeletal reorganization. The fundamental cellular signaling cascade involved in these processes, the phosphatidylinositol 3-kinase/protein kinase-B/mammalian target of rapamycin (PI3K/AKT/mTOR), closely related to the mitogen-activated protein kinase (MAPK) pathway, is a crucial and intensively explored intracellular signaling pathway in tumorigenesis. Various activating mutations in oncogenes together with the inactivation of tumor suppressor genes are found in diverse malignancies across almost all members of the pathway. Substantial progress in uncovering PI3K/AKT/mTOR alterations and their roles in tumorigenesis has enabled the development of novel targeted molecules with potential for developing efficacious anticancer treatment. Two approved anticancer drugs, everolimus and temsirolimus, exemplify targeted inhibition of PI3K/AKT/mTOR in the clinic and many others are in preclinical development as well as being tested in early clinical trials for many different types of cancer. This review focuses on targeted PI3K/AKT/mTOR signaling from the perspective of novel molecular targets for cancer therapy found in key pathway members and their corresponding experimental therapeutic agents. Various aberrant prognostic and predictive biomarkers are also discussed and examples are given. Novel approaches to PI3K/AKT/mTOR pathway inhibition together with a better understanding of prognostic and predictive markers have the potential to significantly improve the future care of cancer patients in the current era of personalized cancer medicine.
Keywords: PI3K pathway; Phosphatidylinositol 3-Kinase; cílená molekulární terapie; protinádorové látky; Neoplasms; racionální návrh léčiv; signální transdukce; inhibitory fosfoinositid-3-kinasy; protoonkogenní proteiny c-akt; TOR serin-threoninkinasy; Phosphoinositide-3 Kinase Inhibitors; Proto-Oncogene Proteins c-akt; inhibitory proteinkinas; Signal Transduction; TOR Serine-Threonine Kinases; Predictive biomarkers; Animals; Targeted therapy; lidé; Humans; zvířata; Protein Kinase Inhibitors; Molecular Targeted Therapy; Drug Design; nádory; 1-fosfatidylinositol-3-kinasa; Antineoplastic Agents